Six weeks of isometric resistance training led to evidence of corticospinal but not reticulospinal adaptation in previously untrained adult males - Simon Walker; Katherine E. J. Keogh; Meghan Tanel; Aidan S. W. Baker; Anne M. E. Baker; Dawson J. Kidgell; Stuart N. Baker (Experimental Brain Research, 2026)
The latest hypothesis regarding the source of enhanced neural activation from resistance training is the reticulospinal rather than the corticospinal tract, based on invasive animal and emerging human data. The present study employed a six-week isometric resistance training intervention in a randomized controlled design to address this knowledge gap. Thirty-nine healthy, untrained males (age ~23 y, sustained contraction group n = 13, explosive contraction group n = 9, control group n = 17) underwent neuromuscular and electrophysiological testing and completed all study requirements. Maximal isometric torque (MVC) and rate of torque development (RTD) were measured during a familiarization session as well as before and after the six-week period. Transcranial magnetic stimulation was used to assess motor-evoked potential (MEP) area and silent period duration while subjects contracted to 10% of MVC. Loud sound (120 dB) was used to modulate MEP area and reaction time to visual stimuli during the StartReact test. Only the intervention groups demonstrated significant improvements in MVC (27%) and RTD (60%) (both P < 0.01), along with reduced MEP area (− 21%) and silent period duration (− 23%) (both P < 0.01). The sustained contraction group showed reduced modulation of reaction time and increased MEP suppression due to loud sound. Short-term resistance training seemed to reduce cortical inhibition and corticospinal excitability in both training groups. The study showed conflicting changes in measures purported to evaluate reticulospinal functioning. It is recommended to examine different forms of resistance training and longer training exposure in future.

A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

Factors influencing public willingness to participate in population-based hereditary cancer genetic testing: a qualitative study of public preferences - Diego R. Sanchez-Vazquez; Jonathan Avery; Whitney Qualls; Colene Bentley; Helen McTaggart-Cowan; Julianne McLeod; Lesa Dawson; Stuart Peacock (Familial Cancer, 2026)

Reticulospinal and corticospinal responses in long-term strength-trained and untrained adults - Meghan Tanel; Dawson J. Kidgell; Sakari Vekki; Juha P. Ahtiainen; Gonzalo Gomez-Guerrero; Eeli J. Halonen; Stuart N. Baker; Simon Walker (European Journal of Applied Physiology, 2025)
Purpose Studies investigating neural adaptation to strength training have yet to determine the loci of previously observed improvements in motor pathway function. While transcranial magnetic stimulation (TMS) studies have typically focused on the corticospinal tract, recent evidence from primates suggests that the subcortical reticulospinal tract may be the primary candidate for adaptation. Methods: Using a cross-sectional comparison, long-term strength-trained athletes ( n = 15, 11M/4F, 32 ± 6 y) and untrained adults ( n = 18, 11M/7F, 32 ± 4 y) underwent a series of neurophysiological tests designed to target corticospinal and reticulospinal functioning based on biceps brachii muscle responses. The StartReact test was used to determine reaction time, rate of torque development, and muscle activity in response to visual (V), visual–auditory (VA, 80 dB), and visual–startle (VS, 120 dB) cues. Reaction times were used to calculate reticulospinal gain ([V–VS]/[V–VA]). Neuro-navigated monophasic TMS to the motor cortex was given during low-force level isometric voluntary contractions (10% of maximum) with both posterior–anterior (100–180% active motor threshold) and anterior–posterior currents (120% active motor threshold). Motor evoked potentials (MEPs) from stimuli given at 120% active motor threshold were compared to startle cue-conditioned responses and anterior–posterior current responses. Results: Untrained adults benefitted more from StartReact (reticulospinal gain, p = 0.003), whereas strength-trained athletes showed greater MEP size at higher stimulation intensities (180% active motor threshold, p = 0.048, 140–180% area-under-the-curve, p = 0.020) and shorter silent period (180% active motor threshold, p = 0.035). Conclusions: Evidence provided here suggests greater cortico-reticulospinal excitability/functioning in long-term strength-trained athletes.

Surface urban heat island variations under the 3-decadal urban expansion in China: Patterns and driving factors - Haibo Yang; Zhengrong Wu; Shike Qiu; Fan Wu; Richard J. Dawson; Alistair Ford; Stuart Barr (Sustainable Cities and Society, 2025)

Microplastics in agricultural soils following sewage sludge applications: Evidence from a 25-year study - Stuart J.F.F. Ramage; Malcolm Coull; Patricia Cooper; Colin D. Campbell; Radhakrishna Prabhu; Kyari Yates; Lorna A. Dawson; Sandhya Devalla; Eulyn Pagaling (Chemosphere, 2025)

Quantifying surface urban heat island variations and patterns: Comparison of two cities in three-stage dynamic rural–urban transition - Haibo Yang; Zhengrong Wu; Richard J. Dawson; Stuart Barr; Alistair Ford; Yunfei Li (Sustainable Cities and Society, 2024)

Factors influencing migration of short‐finned eels ( Anguilla australis ) over 3 years from a wetland system, Lake Condah, south‐east Australia, downstream to the sea - Wayne Koster; Ben Church; David Crook; David Dawson; Ben Fanson; Justin O'Connor; Ivor Stuart (Journal of Fish Biology, 2024)
Anguillid eel populations are under threat globally. A particularly vulnerable life‐cycle stage is the migration of mature adult eels downstream from freshwater habitats through estuaries into the sea to spawn. This study investigated the factors associated with downstream migration of the short‐finned eel Anguilla australis (Richardson 1841) from a coastal wetland (Lake Condah) in south‐east Australia, using acoustic telemetry. Migration was associated with time of the year, higher water level and river flows, decreasing water temperature, and darker moon phases. Larger individuals and those in better condition were more likely to migrate from the wetland. Downstream migration peaked in spring, in contrast to the typical autumn migration period for other temperate anguillids. Variable responses, in comparison to other studies, highlight how migration cues may not be universal. In south‐east Australia, short‐finned eels may have evolved to migrate in multiple phases by first migrating to the estuary during typical seasonal spring flow pulses (e.g., to avoid being stranded in upland reaches during dry summer periods) and then migrating into the ocean in autumn. More research is needed to unravel these processes and causes, especially considering that the relationship between migration and hydrology may be complex and confounded (e.g., by human‐induced disruptions to migratory pathways).

Knowledge and values drive acceptability of lethal control of kangaroos among the Australian public - Stuart Dawson; Courtenay Dawson; Malcolm S. Kennedy; Tracey L. Kreplins; John D.C. Linnell; Patricia A. Fleming (Biological Conservation, 2024)

Why humans kill animals and why we cannot avoid it - Benjamin L. Allen; Christopher Bobier; Stuart Dawson; Peter J.S. Fleming; Jordan Hampton; David Jachowski; Graham I.H. Kerley; John D.C. Linnell; Kelly Marnewick; Liaan Minnie; Mike Muthersbaugh; M. Justin O'Riain; et al. (Science of The Total Environment, 2023)

Extensive regional variation in the phenology of insects and their response to temperature across N orth A merica - Peter O. Dunn; Insiyaa Ahmed; Elise Armstrong; Natasha Barlow; Malcolm A. Barnard; Marc Bélisle; Thomas J. Benson; Lisha L. Berzins; Chloe K. Boynton; T. Anders Brown; Melissa Cady; Kyle Cameron; et al. (Ecology, 2023)
Climate change models often assume similar responses to temperatures across the range of a species, but local adaptation or phenotypic plasticity can lead plants and animals to respond differently to temperature in different parts of their range. To date, there have been few tests of this assumption at the scale of continents, so it is unclear if this is a large‐scale problem. Here, we examined the assumption that insect taxa show similar responses to temperature at 96 sites in grassy habitats across North America. We sampled insects with Malaise traps during 2019–2021 ( N = 1041 samples) and examined the biomass of insects in relation to temperature and time of season. Our samples mostly contained Diptera (33%), Lepidoptera (19%), Hymenoptera (18%), and Coleoptera (10%). We found strong regional differences in the phenology of insects and their response to temperature, even within the same taxonomic group, habitat type, and time of season. For example, the biomass of nematoceran flies increased across the season in the central part of the continent, but it only showed a small increase in the Northeast and a seasonal decline in the Southeast and West. At a smaller scale, insect biomass at different traps operating on the same days was correlated up to ~75 km apart. Large‐scale geographic and phenological variation in insect biomass and abundance has not been studied well, and it is a major source of controversy in previous analyses of insect declines that have aggregated studies from different locations and time periods. Our study illustrates that large‐scale predictions about changes in insect populations, and their causes, will need to incorporate regional and taxonomic differences in the response to temperature.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Learning Together for and with the Martuwarra Fitzroy River - Rosemary Hill; Pia Harkness; Nat Raisbeck-Brown; Ilisapeci Lyons; Jorge G. Álvarez-Romero; Milena Kiatkoski Kim; Dennis Chungalla; Heather Wungundin; Mary Aiken; Jean Malay; Bernadette Williams; Rachel Buissereth; et al. (Sustainability Science, 2022)
Co-production across scientific and Indigenous knowledge systems has become a cornerstone of research to enhance knowledge, practice, ethics, and foster sustainability transformations. However, the profound differences in world views and the complex and contested histories of nation-state colonisation on Indigenous territories, highlight both opportunities and risks for Indigenous people when engaging with knowledge co-production. This paper investigates the conditions under which knowledge co-production can lead to improved Indigenous adaptive environmental planning and management among remote land-attached Indigenous peoples through a case study with ten Traditional Owner groups in the Martuwarra (Fitzroy River) Catchment in Western Australia’s Kimberley region. The research team built a 3D map of the river and used it, together with an interactive table-top projector, to bring together both scientific and Indigenous spatial knowledge. Participatory influence mapping, aligned with Traditional Owner priorities to achieve cultural governance and management planning goals set out in the Fitzroy River Declaration, investigated power relations. An analytical framework, examining underlying mechanisms of social learning, knowledge promotion and enhancing influence, based on different theories of change, was applied to unpack the immediate outcomes from these activities. The analysis identified that knowledge co-production activities improved the accessibility of the knowledge, the experiences of the knowledge users, strengthened collective identity and partnerships, and strengthened Indigenous-led institutions. The focus on cultural governance and management planning goals in the Fitzroy River Declaration enabled the activities to directly affect key drivers of Indigenous adaptive environmental planning and management—the Indigenous-led institutions. The nation-state arrangements also gave some support to local learning and decision-making through a key Indigenous institution, Martuwarra Fitzroy River Council. Knowledge co-production with remote land-attached Indigenous peoples can improve adaptive environmental planning and management where it fosters learning together, is grounded in the Indigenous-led institutions and addresses their priorities.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Diverse effects of the common hippopotamus on plant communities and soil chemistry - Douglas J. McCauley; Stuart I. Graham; Todd E. Dawson; Mary E. Power; Mordecai Ogada; Wanja D. Nyingi; John M. Githaiga; Judith Nyunja; Lacey F. Hughey; Justin S. Brashares (Oecologia, 2018)

Determining the potential sites of neural adaptation to cross-education: implications for the cross-education of muscle strength - Ashlyn K. Frazer; Alan J. Pearce; Glyn Howatson; Kevin Thomas; Stuart Goodall; Dawson J. Kidgell (European Journal of Applied Physiology, 2018)

Prioritizing islands for the eradication of invasive vertebrates in the United Kingdom overseas territories - Jeffrey Dawson; Steffen Oppel; Richard J. Cuthbert; Nick Holmes; Jeremy P. Bird; Stuart H. M. Butchart; Dena R. Spatz; Bernie Tershy (Conservation Biology, 2015)
Invasive alien species are one of the primary threats to native biodiversity on islands worldwide. Consequently, eradicating invasive species from islands has become a mainstream conservation practice. Deciding which islands have the highest priority for eradication is of strategic importance to allocate limited resources to achieve maximum conservation benefit. Previous island prioritizations focused either on a narrow set of native species or on a small geographic area. We devised a prioritization approach that incorporates all threatened native terrestrial vertebrates and all invasive terrestrial vertebrates occurring on 11 U.K. overseas territories, which comprise over 2000 islands ranging from the sub‐Antarctic to the tropics. Our approach includes eradication feasibility and distinguishes between the potential and realistic conservation value of an eradication, which reflects the benefit that would accrue following eradication of either all invasive species or only those species for which eradication techniques currently exist. We identified the top 25 priority islands for invasive species eradication that together would benefit extant populations of 155 native species including 45 globally threatened species. The 5 most valuable islands included the 2 World Heritage islands Gough (South Atlantic) and Henderson (South Pacific) that feature unique seabird colonies, and Anegada, Little Cayman, and Guana Island in the Caribbean that feature a unique reptile fauna. This prioritization can be rapidly repeated if new information or techniques become available, and the approach could be replicated elsewhere in the world. Priorización de Islas para la Erradicación de Vertebrados Invasores en los Territorios Exteriores del Reino Unido

Potential impact of invasive alien species on ecosystem services provided by a tropical forested ecosystem: a case study from Montserrat - Kelvin S.-H. Peh; Andrew Balmford; Jennifer C. Birch; Claire Brown; Stuart H. M. Butchart; James Daley; Jeffrey Dawson; Gerard Gray; Francine M. R. Hughes; Stephen Mendes; James Millett; Alison J. Stattersfield; et al. (Biological Invasions, 2015)

An evaluation of thermal Earth observation for characterizing urban heatwave event dynamics using the urban heat island intensity metric - Tomas Holderness; Stuart Barr; Richard Dawson; Jim Hall (International Journal of Remote Sensing, 2013)

Sexual segregation in distribution, diet and trophic level of seabirds: insights from stable isotope analysis - Richard A. Phillips; Rona A. R. McGill; Deborah A. Dawson; Stuart Bearhop (Marine Biology, 2011)

Isolation, characterisation and predicted genome locations of Light-bellied Brent goose (Branta bernicla hrota) microsatellite loci (Anatidae, AVES) - Xavier A. Harrison; Deborah A. Dawson; Gavin J. Horsburgh; Tom Tregenza; Stuart Bearhop (Conservation Genetics Resources, 2010)

Population genetic analysis of a recent range expansion: mechanisms regulating the poleward range limit in the volcano barnacle Tetraclita rubescens - MICHAEL N. DAWSON; RICHARD K. GROSBERG; YOEL E. STUART; ERIC SANFORD (Molecular Ecology, 2010)

Stable isotopes reveal individual variation in migration strategies and habitat preferences in a suite of seabirds during the nonbreeding period - Richard A. Phillips; Stuart Bearhop; Rona A. R. Mcgill; Deborah A. Dawson (Oecologia, 2009)

Does variation in workload affect fatigue in a regular 12-hour shift system? - Stuart D BAULK; Katie J KANDELAARS; Nicole LAMOND; Gregory D ROACH; Drew DAWSON; Adam FLETCHER (Sleep and Biological Rhythms, 2007)

Observations of age-related differences in neurobehavioral performance in a 12-hour shift system - Katie J KANDELAARS; Stuart D BAULK; Adam FLETCHER; Guy EITZEN; Gregory D ROACH; Drew DAWSON (Sleep and Biological Rhythms, 2006)

Influence of Tree Species on Forest Nitrogen Retention in the Catskill Mountains, New York, USA - Pamela H. Templer; Gary M. Lovett; Kathleen C. Weathers; Stuart E. Findlay; Todd E. Dawson (Ecosystems, 2005)

The 26S-proteasome: regulation and substrate recognition - Simon Dawson; Richard Hastings; Katsuhiko Takayanagi; Stuart Reynolds; Peter Løw; Michael Billett; R. John Mayer* (Molecular Biology Reports, 1997)